2016
DOI: 10.1016/j.celrep.2016.10.047
|View full text |Cite
|
Sign up to set email alerts
|

DIXDC1 Phosphorylation and Control of Dendritic Morphology Are Impaired by Rare Genetic Variants

Abstract: The development of neural connectivity is essential for brain function, and disruption of this process is associated with autism spectrum disorders (ASDs). DIX domain containing 1 (DIXDC1) has previously been implicated in neurodevelopmental disorders, but its role in postnatal brain function remains unknown. Using a knockout mouse model, we determined that DIXDC1 is a regulator of excitatory neuron dendrite development and synapse function in the cortex. We discovered that MARK1, previously linked to ASDs, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…These results are consistent with recent genotyping analysis of the MARK1 (microtubule affinity‐regulating kinase 1)‐tagged‐SNP, identifying several SNPs within this gene, in particular, were associated with ASDs . Kwan et al recently reported that MARK1‐mediated phosphorylation of DIXDC1 plays an important role in regulating dendrite and spine development and that the rare missense variants in DIXDC1 identified in ASD subjects via genetic sequencing precluded this activity, thus contributing to impaired dendritic morphology. Martin et al extended the role that SNPs in DIXDC1 isoform may have in psychiatric pathogenesis by suggesting that such SNPs in psychiatric populations, like ASD and schizophrenia, may modulate Wnt/β‐catenin signaling activity.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with recent genotyping analysis of the MARK1 (microtubule affinity‐regulating kinase 1)‐tagged‐SNP, identifying several SNPs within this gene, in particular, were associated with ASDs . Kwan et al recently reported that MARK1‐mediated phosphorylation of DIXDC1 plays an important role in regulating dendrite and spine development and that the rare missense variants in DIXDC1 identified in ASD subjects via genetic sequencing precluded this activity, thus contributing to impaired dendritic morphology. Martin et al extended the role that SNPs in DIXDC1 isoform may have in psychiatric pathogenesis by suggesting that such SNPs in psychiatric populations, like ASD and schizophrenia, may modulate Wnt/β‐catenin signaling activity.…”
supporting
confidence: 88%
“…N 2 O exposure is known to antagonize NMDA receptor activation, thus simulating many of the downstream signaling deficits attributed to specific, rare genetic variants in ASD . Moreover, I have highlighted how low dose N 2 O exposure may enhance opioidergic activity through induction of central dynorphin release, an endogenous ligand of the kappa opioid receptor (KOR), and contribute to altered behavioral stereotypy, abnormal gait, socio‐communicative deficits, as well as synesthesia experiences in ASD .…”
mentioning
confidence: 99%
“…MARK1 is involved in neuronal migration by phosphorylating doublecortin, MAP2 and tau [39]. Through phosphorylating PSD95 [40] or DIX domain containing 1 (DIXDC1) [41], MARK1 plays essential roles in dendritic spine morphogenesis. It is overexpressed in the prefrontal cortex of autistic patients and proposed as a susceptibility gene for autism [37].…”
Section: Resultsmentioning
confidence: 99%
“…These proteins are involved in highly active biological processes in the immature brain, which include neural progenitor proliferation and neurogenesis (BRCA2, CHMP1A, SNF2L1 and TLR3), neuronal migration (JIP1 and MARK1), neurite extension (JIP1, MARK1, SNF2L1 and TLR3), or dendrite/synapse development or functioning (MARK1 and SESTD1). Among these proteins, MARK1 and SESTD1 were proven to be localized at PSDs [41,48], whereas the presence and specific roles for the other five proteins at postsynaptic site require further clarification.…”
Section: Discussionmentioning
confidence: 99%
“…Several Wnt ligands have been implicated in dendritogenesis in vitro (Wayman et al, 2006;Hiester et al, 2013). Most of them act through non-canonical, b-catenin-independent pathways, regulating cytoskeleton organization and dynamics, both in vitro (Rosso et al, 2005;Terabayashi et al, 2007;Hagiwara et al, 2014;Okerlund et al, 2016;Kwan et al, 2016) and in vivo (Gonç alves et al, 2016;Chen et al, 2017;Lanoue et al, 2017). Here, we demonstrate that canonical Wnt transcriptional activity has a dual role in dendritic development, depending on the developmental stage of neurons, during two specific time windows: first, between E21 and P7 it promotes dendritic growth and branching, as well as spine formation; later, between P21 and P30 it only regulates spine formation.…”
Section: Discussionmentioning
confidence: 99%